The population and family health project = (The World Bank in Vietnam (WB), 2003)
The overall purpose of the Population and Family Health Project is to support the strengthening and revitalization of the family health and family planning sector, thereby improving the health status of the population and bringing a further reduction in fertility and population growth. The project will operate at two levels, the first national and the second in a selected group of15 provinces. The project's objectives are: a) to increase utilization of family planning and related family health services; b) to improve the quality and range of family planning and related family health services; c) to enhance the National Committee for Population and Family Planning's (NCPFP) management, planning and policy formulation capabilities; and d) to expand the knowledge base on which policy and technical guidelines would be founded. For the selected 15 provinces, the focus will be on strengthening of the Primary Health Care (PHC) system at commune and district levels, with a particular emphasis on Maternal and Child Health (MCH) and family planning services. The project consists of five components, of which four are national in scope and focused on family planning and the fifth covers the primary health care system (commune and district-level). These components consist of: service delivery; information, education and communication; contraceptive supplies, family planning management and institutional development; and service delivery model initiative.